2016
DOI: 10.1002/cncr.29976
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human papillomavirus type 16 in oropharyngeal squamous cell carcinoma using droplet digital polymerase chain reaction

Abstract: BACKGROUND:The incidence of oropharyngeal squamous cell carcinoma caused by oncogenic HPV (HPV-OPSCC) is rising worldwide. HPV-OPSCC is commonly diagnosed by RT-qPCR of HPV-16 E6 and E7 oncoproteins or by cyclin-dependent kinase inhibitor 2A, multiple tumor suppressor 1 (p16) immunohistochemistry (IHC). Droplet digital PCR (ddPCR) has been recently reported as ultrasensitive and highly precise method of nucleic acid quantification for biomarker analysis. We aimed to validate this method for the detection of HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 66 publications
5
52
0
Order By: Relevance
“…Finally, several recent studies have shown that a saliva-based assay can be used as a post-treatment surveillance tool because the presence of HPV DNA after treatment is associated with a higher risk of recurrence [2224]. While the sensitivity of our assay was similar to these studies, it was significantly lower than studies which measured HPV DNA directly in tumoral tissue [25]. As a result of its modest sensitivity but high specificity, a saliva based assay is best suited for confirming the presence of a clinically occult oropharyngeal tumour and monitoring for recurrence of an HPV positive tumour after treatment.…”
Section: Discussionmentioning
confidence: 51%
“…Finally, several recent studies have shown that a saliva-based assay can be used as a post-treatment surveillance tool because the presence of HPV DNA after treatment is associated with a higher risk of recurrence [2224]. While the sensitivity of our assay was similar to these studies, it was significantly lower than studies which measured HPV DNA directly in tumoral tissue [25]. As a result of its modest sensitivity but high specificity, a saliva based assay is best suited for confirming the presence of a clinically occult oropharyngeal tumour and monitoring for recurrence of an HPV positive tumour after treatment.…”
Section: Discussionmentioning
confidence: 51%
“…Over the past decade, the incidence of HPV-related OPSCC has been rising worldwide [17]. When compared to non-HPV related OPSCC, HPV-OPSCC is molecularly distinct and patients with these tumors have improved survival outcomes regardless of treatment modality [820].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the use of HPV 16 E6/E7 qPCR as an analytical and surveillance tool for cervical, head and neck, and oropharyngeal and cancers . However, there is lack of data to detect the HPV 16 E6/E7 DNA expression in OSCC samples using the qPCR technique.…”
Section: Discussionmentioning
confidence: 99%